2011
DOI: 10.1007/s10751-011-0461-y
|View full text |Cite
|
Sign up to set email alerts
|

Gas counter for low temperature Conversion Electron Mössbauer Spectroscopy experiments

Abstract: The operation of a gas counter, designed for Conversion Electron Mössbauer Spectroscopy measurement at low temperature, has been investigated. The experimental setup is described and tested with two pure gases, He and Ne, and two mixtures, He-5%CH 4 and He-5%N 2 . The impacts on the counter performances of the applied voltage, the gas composition and pressure as well as the gas renewing are investigated between 41 K and 300 K. This investigation is made using 119 Sn Mössbauer source and metallic tin absorber. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The samples were then transferred into a CEMS gas counter. 32 Both spectra consist mainly of Sn(IV) and Sn(0) emissions similar to those observed for the non-cycled material. It is worth noting that in the case of 119 Sn, the depth of CEMS analysis is around 2-3 mm, meaning that the obtained spectra are representative of the whole layer of Ti 1/2 Sn 1/2 O 2 nanotubes.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The samples were then transferred into a CEMS gas counter. 32 Both spectra consist mainly of Sn(IV) and Sn(0) emissions similar to those observed for the non-cycled material. It is worth noting that in the case of 119 Sn, the depth of CEMS analysis is around 2-3 mm, meaning that the obtained spectra are representative of the whole layer of Ti 1/2 Sn 1/2 O 2 nanotubes.…”
Section: Resultssupporting
confidence: 59%
“…A specic helium-ow counter was used for the detection of conversion electrons. 32 The g-ray source consisted of Ba 119m SnO 3 with a nominal activity of 7 mCi. The hyperne parameters, isomer shi (d) and quadrupole splitting (D), were determined by tting appropriate Lorentzian lines to the experimental data.…”
Section: Methodsmentioning
confidence: 99%
“…CEMS measurements were performed in normal incidence using a home-made gas flow (He − CH 4 ) proportional counter 45 . For the measurements at low temperatures, the counter was mounted inside a closed-cycle He cryostat 46 . The source was 57 Co in Rh matrix of about 1.85 GBq activity, mounted in a velocity transducer operating in constant acceleration mode.…”
Section: Mössbauer Spectrometrymentioning
confidence: 99%
“…Sougrati et al reported on gas flow counters with gas renewing to enable stable counter performance over a long period. 13 This setup was based on a closed cycle refrigerator cryostat (commercially available) and allowed to measure Mössbauer spectra down to 41 K. Fukumura et al reported stable operation of gas detectors from 300 K to 15 K using hydrogen gas. 14 Among gaseous detectors, improved signal-to-noise ratio and faster time response can be obtained using parallel plate avalanche detectors (PPADs).…”
Section: Introductionmentioning
confidence: 99%